The Role of Lactate Clearance in Severe Septic Patients Survival - Hambali, Wirawan; Chen, Lie Khie; Widodo, Djoko; Dewiasty, Esthika; Pohan, Herdiman T.; Suhendro, Suhendro (Jurnal Penyakit Dalam Indonesia, 2016)
Introduction. Severe Sepsis is a major health problem that known to results high mortality rate, and still its incidents continue to rise. Lactate clearance represents kinetics alteration of anaerobic metabolism in severe septic patients that makes it to become a potential parameter to evaluate severity of one’s illness and intervention adequacy that received by the patient. However, the relationship between lactate clearance and occurrence of death in severe septic patients is still unknown. Methods. This is a prospective cohort study that conducted in Ciptomangunkusumo Hospital, from March to May 2011. Patients were categorized into high lactate clearance group if there were differences in lactate levels ≥ 10% in which occurred within the first 6 hours of the treatment, and contrary were categorized into low lactate clearance group. Occurrences of death were observed within the first 10 days. Afterward, the data were analyzed by means of survival analysis, Kapplan Meier curve were made, survival rate and median survival rate were determined, statistical test were calculated using log-rank test, and hazard ratios were calculated using Cox regression model test. Analysis of Confounder Variable was also performed using multivariate Cox regression test. Results. The survival rate for high and low lactate clearance group were 60.0% vs. 26.7%, respectively (p=0,004). In low lactate clearance group the median survival was 3 days, while the mortality rate did not reach 50% in high lactate clearance group. The first Interquartile for these two groups was 1 day and 4 days, respectively. The hazard ratio that obtained from the analysis was 2.87 (95% CI, 1.41 - 5.83). On multivariate analysis the presence of septic shock, SOFA score, the use of vasopresor/inotropic, blood transfusion, fluid resuscitation didn’t change the hazard ratio value more than 10%. For that reason, these parameters were not considered as confounder. Conclusions. Patients with high lactate clearance have a better survival rate compared to patients with low lactate clearance, and its relationship is not influenced by confounder.